Upaya Mewujudkan Mutu Pendidikan Agama Islam Melalui Kegiatan Ekstrakurikuler Keagamaan: Studi Kasus di Madrasah Aliyah Darussalam Nganjuk - Huda, Muhamad Nur (Lembaga Penelitian, Publikasi dan Pengabdian Masyarakat (LP3M) UIT Lirboyo Kediri, 2022)
One of the efforts to improve the quality of one's life and personality is education. Among the problems being faced by the Indonesian people is the moral decadence that occurs in this nation. In Indonesia, Islamic education has been included in the formal school education curriculum. However, over time, Islamic education in schools is still considered to be less effective in realizing students with noble character. For this reason, it is necessary to take concrete steps that must be taken by educators to overcome the moral crisis that is still happening. One of these steps is to provide additional hours in the form of religious extracurricular activities. This study uses a qualitative descriptive-analytical approach and the type of research used is a case study. There are three types of procedures in data collection techniques, namely: observation and participation; interview; and documentation. Technical data analysis is an interactive analysis from Miles and Huberman in which the researchers carried out three stages, namely: data reduction; data display; and drawing conclusions and verification. The results of this research are: (1) MA Darussalam Nganjuk uses the 2013 curriculum (K-13) Islamic Education material that prioritizes students' cognitive, affective, and psychomotor. There are two kinds of religious extracurricular activities at MA Darussalam Nganjuk, namely: mandatory religious extracurricular activities, namely: Study of the Yellow Book (K3), and selected religious extracurricular activities, namely: Khitabah, the art of recitation of the Holy Quran, and art of hadrah. (2) The application of religious extracurricular activities at MA Darussalam Nganjuk has been able to realize the quality of Islamic Education taught in extracurricular activities in the classroom. This is based on the results of research in the form of observations, interviews, and documentation that have been carried out by the researcher.